Risken med riskkalkyler: exemplet ärftlig bröstcancer i sociologisk belysning (Sociologisk Forskning, 2001)
This article addresses risk construction in texts concerning genetic counselling, both in medical and lay contexts. The main focus is how the medical perspective presents genetic risk as being ”objective”, statistically precise and at a high level. Risk is being presented as constituted by two dimensions; probability of impact and age. Furthermore, the discussion includes the labelling of ”at-risk”, a construction of a category of potentially sick. Risk in lay texts is analysed as multidimensional, consisting of; probability of impact, fear of cancer, experience from cancer in the family, responsibility for own children, cultural implications of genetics as well as trust in doctors and expert systems. The concept of risk and probability in various texts is being analysed within a framework of mainstream social scientific theories on risk. Finally the article ends up with a discussion of the relationship between risk and gender in the context of the potentially sick woman in genetic counselling.
Keywords: risk; breast cancer; genetic counselling; genetics; gender